Pengembangan Permainan Baseball Pass Sebagai Penunjang Latihan Passing Pada Siswa Ekstrakurikuler Bola Basket SMA Negeri 1 Ponorogo - Bayu Nugraha Murdiansyah (CV. Multi Kreasi Media, 2025)
Lack of variative exercise models in the extracurricular sman-ballbasket-basketting activities. 1 ponorogo, especially the basic technical passing and causing a lack of understanding and mastery about passing basketball..Then it takes the development of this game to improve the understanding and mastery of the extracurricular basketball about basic passing techniques. This research aims to develop a product of basketball passing through baseball pass games for the student's extracurricular basketball state 1 ponorogo. This is the method the methodology referring to research development model of development of r amp d &; addie was by using the method, namely: ( ) analize ( 1 2 3 ) development ( ) design ( 5 4 ) implementation ( ) evaluation. Based on research obtained that the game baseball pass is used as supporting training students passing extracurricular basketball. Proved from the test results obtained the expert Evauation data which is, player 86 % (good), 88 basketball expert % (good), Test small group 84.7 % (good).Both of these trials got good category value and could be used. With the result, it can be concluded that the game baseball pass can be used as supporting training students passing extracurricular basketball schools ponorogo 1.